P The Effect of Teacher Praise on Students’ Psychological Well Being at SMPN 18 Muaro Jambi - Amanda, Restu; Sutja, Akmal; Sarman, Freddi (The Future of Education Journal, 2026)
This study is motivated by the importance of students’ psychological well-being in supporting the learning process at school. One factor presumed to influence it is teacher praise. Therefore, this study aims to determine the effect of teacher praise on students’ psychological well-being at SMPN 18 Muaro Jambi in the 2025/2026 academic year. This research employed a quantitative approach with an ex post facto method. Data were collected through questionnaires distributed to students as the research instrument. The subjects of this study were students of SMPN 18 Muaro Jambi. The data were then analyzed using statistical analysis with the assistance of SPSS software. The results showed that teacher praise was in the high category (71.3%), with verbal praise at 75.4% and nonverbal praise at 66.7%. Students’ psychological well-being was also in the high category (68.1%). The analysis results indicate that there is an effect of teacher praise on students’ psychological well-being. Thus, the better the praise given by teachers, the better the psychological well-being of students at school.